The Role and Significance of Intercultural Competence in the Work of Contemporary Managers. Polish Managers’ Opinion - Agnieszka KNAP-STEFANIUK; Łukasz BURKIEWICZ (Communications of International Proceedings, 2021)
The continuously growing role of international cooperation results in an increased interest in intercultural competence of contemporary managers, as such competence greatly affects management of multicultural teams and cooperation with culturally diverse groups of customers. Effective intercultural cooperation requires well-developed adaptive skills, the ability to deal successfully with a range of experiences linked to crossing cultural barriers, sensitivity to other cultures and, above all, full awareness of cultural diversity of the contemporary world and working environments, especially those linked to international business. The purpose of the article is to analyse the role and significance of intercultural competence in the work of contemporary managers. The authors argue that nowadays this competence is crucial as it affects the quality of teamwork in multicultural environments, managers’ ability to understand and accept cultural diversity of their employees, and positive relationships with employees and customers who come from different cultures. In the first part of the article, the term “competence’ is defined and the significance of managers’ competences in contemporary management is presented. The next part is devoted to the analysis of intercultural competence and its role in management in multicultural working environments. Finally, the article reports the results of the study on the role and significance of intercultural competence of contemporary managers. The study (i.e. the interviews) was conducted among Polish managers with at least three years of experience of working in international companies. The interviews and the review of the subject literature reveal the vital role played by intercultural competence in the work of contemporary managers, as it exerts a great impact on various aspects of management in a culturally diverse working environment.
Keywords: Competences; Intercultural Competence; Contemporary Manager; Cultural Diversity; Multiculturalism.